Designing a model for development of women sports with an emphasis on sports as a social phenomenon: What do we need? - Hekmati, M.; Dinani, M. M.; Hosseini, R. N. S. (Journal of Human Sport & Exercise, 2020)
Despite the development of sports in Iran, women's sports have not yet been able to achieve a desirable position. The development components and their necessary contexts and backgrounds must be identified to achieve the development of women sports. The aim of this study was to present a model for development of women's sports in Iran which was conducted through qualitative research method with the fundamental-exploratory nature. The data were collected by snowball sampling method based on deep interviews, which were coded and analysed according to grounded theory with a constructive approach. The results showed that the development of women's sports involves three components: environmental, structural, and behavioural. Furthermore, there was an intimate relationship between all the developmental contexts. Also, Peripheral components were identified as a large-scale context but structural components as facilitating contexts for development. The results also indicated to achieve women Sports development, suitable contexts are needed and the most important one is Cultural-Social context. Based on the results, necessary actions for the development of women's sport should be taken through the establishment of proper policies, determination of appropriate structures, and provision of favourable environments and contexts.